ОНКОЛОГИЧЕСКИЕ ЗАБОЛЕВАНИЯ ПРИ СИНДРОМАХ ХРОМОСОМНОЙ НЕСТАБИЛЬНОСТИ У ДЕТЕЙ В РЕСПУБЛИКЕ БЕЛАРУСЬ - Володащик, Татьяна Петровна; Алешкевич, Светлана Николаевна; Полякова, Екатерина Александровна; Гурьянова, Ирина Евгеньевна; Белевцев, Михаил Владимирович (FORCIPE, 2022)